Greek and Roman Motifs in the Mythology of the Polish-Lithuanian Commonwealth - Joanna Orzeł (CoSMO, 2022)
This article analyses the inspiration for the characters and motifs originating from Greek and Roman mythology in the mythical stories about the beginnings of Poland and Lithuania, from the Polish-Lithuanian Commonwealth formed in 1569. The founding fathers of these states – Lech and Palemon – were often compared to Remus and Romulus, French Faramund or British Brutus of Troy. The most extensive use of antique motifs was made by Jan Skorski, the author of an epic poem about Lech created in 1745. The poet was inspired above all by the Aeneid and the Odyssey. The use of antique motifs by Polish chroniclers and poets was in turn an inspiration for the nobility, who were also “searching” (better: creating) for their antique roots.